Faktor yang Berhubungan dengan Keikutsertaan PUS dalam Ber-KB - Hasanah Pratiwi Harahap (Poltekkes Kemenkes Palu, 2019)
Indonesia is a developing country that has a large population of about 237.6 million people and an average population growth rate of 1.49% per year. In Taraha Village, there are still many couples of reproductive age that are not acceptors, as many as 52 (46.2%). The purpose of this study was to determine the factors associated with couples of reproductive age participation in the family planning program in Taraha Village in 2018. This research was analytic survey research with a cross-sectional approach. The data collection method used questioner. The study was conducted in Taraha Village, Mandrehe Utara Subdistrict, in 2018. The sample of this research was the productive age couples, who were 81 acceptors and not acceptors using a stratified random sampling technique. Data were analyzed by performing a Chi-square analysis test. Based on the results obtained on the knowledge variable the majority of knowledge lacking by 42 respondents (52%) with a p-value <0,001, the majority of negative attitudes as many as 55 respondents (68%) with a p-value of 0.010, the majority of cultural factors were not good enough as many as 44 respondents (54%) obtained a p-value<0,001. It is recommended to the government of Nias Barat District to increase health promotion, especially on the family planning program.